How worthwhile is it to maximise customer satisfaction in public transport service contracts with a large captive user base? The case of South Africa. (September 2018) - Mokonyama, Mathetha; Venter, Christo
Abstract: While improved service quality is critical for improved patronage of public transport services, in markets characterised by large proportions of captive public transport users, typically found in developing or emerging economies, the marginal benefits of improved service quality are not apparent. For cost-conscious public transport operators, therefore, it may be more convenient and logical to keep service improvements at a bare minimum, or to cut services altogether, in order to reduce operating costs. As a follow-up to Mokonyama and Venter (2013), the paper uses historical financial and patronage data from existing bus contracts in South Africa and a conjoint-analysis based behavioural model to estimate the budgetary implications, and marginal benefits, of specifying service quality in public transport contracts. This is especially relevant in an environment like South Africa, in which authorities seek some formulation of Pigouvian subsidy oriented transport policy. It is shown that the marginal benefits of improved service quality can be significant relative to the business as usual alternative. The non-linear response surface characterising the relationship between probability of using a service and the quality of the service implies that increased satisfaction of both captive and non-captive users produces disproportionately higher benefits for both and society.